Language is not a thing: it is a practice! A conversation with Patrick Sériot - E. Israel Chávez Barreto (Sign Systems Studies)
This interview with Patrick Sériot, a scholar of the history and epistemology of linguistic theories, presents some small aspects of his engagement with linguistics in his early years, and thereafter discusses the problem of the interrelationships between culture and language sciences by tackling the question to which extent culture shapes the idea of language and, correspondingly, to which extent such an idea of language shapes linguistic research. The conversation then moves on to the issues of meaning, translation, and the ways of determining the context of a given work, mainly discussing examples of Sériot’s own works. In its final part, the interview deals with the problem of the social commitments of linguistics, and how we, as linguists, may contribute to the solving of social problems.